Determinan Promosi Online dan Dampaknya terhadap Keputusan Pembelian - Hartanti Nugrahaningsih (Jurnal Ekonomi Perusahaan, 2020)
This research aims at "Determinants of Online Promotion of Purchasing Decisions". The dependent variable in this study uses the purchase decision and the mediating variable uses online promotion. The independent variables contain e-WOM and Guerilla Marketing. The online survey method was used for data collection by distributing online questionnaires on the Wardah Beauty website to 200 respondents. By using SmartPLS software to test the validity and reliability of data and the relationship between constructs to test the research hypothesis. This research shows that Wardah's cosmetic customers are millennials, with an average age of 24-39 years. They are a group that relatively familiar with the digital world and active with social media. E-WOM, Guerilla Marketing, and Online Promotion are the latest marketing methods that use a lot of digital and internet technology. It is proven that the online promotions that have been carried out by Wardah cosmetic products are heavily influenced by e-WOM and Guerilla Marketing. The creative messages conveyed and spread by customers through their social media activity. Besides, the surprises were able to attract the attention of customers well. And successful online promotions have had an influence on customers in making purchasing decisions. Thus, it can be estimated that there will be an increase in the sales potential of Wardah's cosmetic products. Keywords: e-WOM, Guerilla Marketing, Online Promotion, Purchasing Decisions